Soil and Mineral Nutrients in Plant Health: A Prospective Study of Iron and Phosphorus in the Growth and Development of Plants - Mujtaba Aamir Bhat; Awdhesh Kumar Mishra; Sheezma Nazir Shah; Mudasir Ahmad Bhat; Saima Jan; Safikur Rahman; Kwang-Hyun Baek; Arif Tasleem Jan (Current Issues in Molecular Biology, 2024)
Plants being sessile are exposed to different environmental challenges and consequent stresses associated with them. With the prerequisite of minerals for growth and development, they coordinate their mobilization from the soil through their roots. Phosphorus (P) and iron (Fe) are macro- and micronutrient; P serves as an important component of biological macromolecules, besides driving major cellular processes, including photosynthesis and respiration, and Fe performs the function as a cofactor for enzymes of vital metabolic pathways. These minerals help in maintaining plant vigor via alterations in the pH, nutrient content, release of exudates at the root surface, changing dynamics of root microbial population, and modulation of the activity of redox enzymes. Despite this, their low solubility and relative immobilization in soil make them inaccessible for utilization by plants. Moreover, plants have evolved distinct mechanisms to cope with these stresses and coregulate the levels of minerals (Fe, P, etc.) toward the maintenance of homeostasis. The present study aims at examining the uptake mechanisms of Fe and P, and their translocation, storage, and role in executing different cellular processes in plants. It also summarizes the toxicological aspects of these minerals in terms of their effects on germination, nutrient uptake, plant–water relationship, and overall yield. Considered as an important and indispensable component of sustainable agriculture, a separate section covers the current knowledge on the cross-talk between Fe and P and integrates complete and balanced information of their effect on plant hormone levels.